Persepsi Masyarakat terhadap Vaksinasi Covid-19: Studi Kualitatif di Indonesia - Yeanneke Liesbeth Tinungki; Nansy Delia Pangandaheng; Chandrayani Simanjorang; Gitalia Putri Medea (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans. The virus that causes is Sars-CoV-2. Vaccination in the community is one of the precautions used to control transmission. The purpose of this study was to determine the public's perception of the covid 19 vaccine in Sangihe Islands Regency. Methods: This study used a phenomenological qualitative research method with in-depth interviews with 30 community members in Kepualuan Sangihe District with purposive sampling technique. The data analysis used refers to the seven steps of the Collaizi data analysis technique. Results: In this study, there are two major themes, namely positive perceptions and negative perceptions. Positive Perceptions include: government efforts, God's guidance, breaking the chain of transmission. Negative perceptions include: anti-chrysalis (666), fear of side effects, vaccine insecurity, fulfillment of the end of time. Conclusion: Public acceptance of the covid 19 vaccine is still lacking, therefore it is hoped that there is a need for socialization about vaccines from health workers so that it can increase the knowledge and understanding of the community that is lacking in vaccine safety.